Harnessing Predictive Power: Exploring the Crucial Role of Machine Learning in Early Disease Detection - Saad Rasool; Ali Husnain; Ayesha Saeed; Ahmad Yousaf Gill; Hafiz Khawar Hussain (CV. Shofanah Media Berkah, 2023)
The incorporation of machine learning into healthcare has transformed the landscape of disease detection, allowing for a paradigm shift from reactive to proactive approaches. This paper investigates the transformative effect of machine learning on early disease detection by conducting a comprehensive literature review. The paper is divided into ten sections, each of which focuses on an important aspect of this developing discipline. The first section, titled